Effects of Different Thermal Processing Methods and Enrichment on The Quality and Consumer Acceptability of Cassava Mash Based Extruded Snacks - A, Obafemi Akinwotu; A, Kehinde Taiwo; A, Victor Ikujenlola (Journal of Food Innovation, Nutrition, and Environmental Sciences)
This study explored effects of heat processing and nutrient enrichment on the qualities of cassava- snacks. The snacks were prepared using three methods, baking, frying, and roasting, and were enriched with cocoa powder and desiccated coconut. Moisture levels ranged between 3.42% and 7.46%. Frying caused some nutrient loss, but enrichment boosted fibre and ash content, especially with desiccated coconut. Fried samples had the highest fat content (4.20% to 16.17%). Although protein levels decreased slightly after frying, enrichment significantly increased it from 4.04% to 12.24%.  Potassium, zinc, calcium, iron, and magnesium also increased with enrichment. However, frying reduced the antioxidant benefits of cocoa powder. Enrichment also affected physical properties, reducing both snack length and lateral spread. Sensory tests showed fried snacks, particularly those with coconut, were the most appealing in taste, texture, and appearance. Overall, while frying improved sensory appeal, baking, and roasting were more effective in preserving nutritional and antioxidant properties.